Nocebo effects in visceral pain: concept and design of the experimental randomized-controlled pain study ‘NoVis’ - Aulenkamp, Jana Luisa; Icenhour, Adriane; Elsenbruch, Sigrid (Frontiers in Psychiatry, 2023)
The role of psychological factors in the pathophysiology and treatment of chronic visceral pain in disorders of gut-brain interactions (DGBI) is increasingly appreciated. Placebo research has underscored that expectations arising from the psychosocial treatment context and from prior experiences shape treatment responses. However, effects of negative expectations, i.e., nocebo effects, as they are likely crucial elements of DGBI patients’ clinical reality, have thus far only rarely been investigated in the context of visceral pain, with untapped potential for improved prevention and treatment. The experimental randomized-controlled pain study “NoVis,” carried out within the Collaborative Research Center (CRC) 289 (“Treatment Expectation”), aims to close gaps regarding the generation and persistence of nocebo effects in healthy volunteers. It is designed to elucidate effects of negative expectations in a multiple-threat paradigm with intensity-matched rectal distensions and cutaneous thermal stimuli, allowing to test nocebo effects in the visceral and somatic pain modalities. Negative expectations are experimentally induced by elements of doctor-patient communication (i.e., instruction) and/or by surreptitious amplification of symptom intensity (i.e., experience/learning) within a treatment context. Accordingly, the repeated measures between-subject design contains the between-group factors “treatment instruction” (negative vs. control) and “treatment experience” (negative vs. control), with volunteers randomized into four experimental groups undergoing several pain stimulation phases (repeated factor). This allows to compare the efficacy of instruction vs. experience, and more importantly, their combined effects on the magnitude of negative expectations and their impact on pain responses, which we expect will be greatest for the visceral modality. After a Baseline, short-term effects are assessed during a test phase accomplished on study day 1 (Test-1 Phase). To explore the persistence of effects, a second test phase is accomplished 1 week later (Test-2 Phase). Effects of negative expectations within and across pain modalities are assessed at the subjective and objective levels, with a focus on psychophysiological and neuroendocrine measures related to stress, fear, and anxiety. Since nocebo effects can play a considerable role in the generation, maintenance, or worsening of chronic visceral pain, and may even constitute risk factors for treatment failure, knowledge from experimental nocebo research has potential to improve treatment outcomes in DGBI and other clinical conditions associated with chronic visceral pain.